Fraud Prevention Of Government Procurement Of Goods And Services In Local Government - Dewi Kusuma Wardani; Anita Primastiwi; Hanisah Hanisah (Jurnal Akuntansi, 2021)
Referring to the government's efforts to prevent fraud, this study aims to provide empirical evidence regarding the effect of the implementation of e-procurement, whistleblowing system, and the Government Internal Control System (SPIP) on the prevention of fraud in the procurement of goods and services. Sampling used purposive sampling technique, and hypothesis testing using the PLS method using the SmartPLS 3 program. Data collection was carried out in May 2019. The research sample was 68 procurement actors who had served at least 1 year in the Procurement Service Unit (ULP), Inspectorate, and Health Office in Yogyakarta City. The results of this study indicate that the application of e-procurement, whistleblowing system, and SPIP has a positive effect on fraud prevention in the process of procuring goods and services in Yogyakarta City.